Anthropolinguistic Analysis of form and Meaning Petung Weton Javanese Society Marriage (London Journal of Research In Humanities and Social Sciences, 2024)
Culture as knowledge  collective,  has  stored  in  minds  every  human.  Function  language  as  practices  culture  among otheralso  forexplains meaning   sayings . Languagecan be said  alsoas wrong one wealth spiritual that  owns  by  a group of  humans  and  together  saidspeech  commmunity.   On ‘s research focused on   studyconducted  atVillage Kesamben  ,Ngadum as wrong one focus study  . On data  interviews thatobtained ,community village Kesamben is still  is very  is thick  will tradition which  has, tradition which  still  maintained  until  now  is  calculation  Petung  Weton  as  wrong  one  thingwhich  is obliged  to be taken into account  to  bride  woman  and  man  when  will  starts  a  lives  new.  In  research  this  uses  study  anthropolinguistics  withfocuses on form and meaning
Keywords: Gender; domestic violence; Violence; Intersectionality; femicide; fundamental rights; positive obligations; family life; Nation; narration; Morocco; theatre; inception; aspects.; Anthropolinguistics; Weton; semiology